2019
DOI: 10.1111/ecc.13123
|View full text |Cite
|
Sign up to set email alerts
|

Time from incident primary cancer until recurrence or second primary cancer: Risk factors and impact in general practice

Abstract: Objective Specialised follow‐up care after cancer treatment is changing towards increased involvement of general practice. To ensure timely detection of new cancer events, knowledge is warranted on the timing of cancer recurrence (CR) and second primary cancer (SPC), including risk factors for CR. Methods This population‐based register study included 67,092 patients diagnosed with malignant melanoma, bladder, lung, ovarian, endometrial, colorectal and breast cancer in Denmark in 2008–2016. The time from primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Similar to our crude estimates, the aforementioned Danish study on breast cancer recurrence reported lower risks in women living alone, also after adjustment for age, education level, comorbidity, calendar period, tumor and lymph node stage, and adjuvant therapy (chemotherapy and/or radiotherapy) [ 8 ]. However, their findings may be affected by residual confounding from other dimensions of SEP, which were not incorporated in their study (e.g., income and employment).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to our crude estimates, the aforementioned Danish study on breast cancer recurrence reported lower risks in women living alone, also after adjustment for age, education level, comorbidity, calendar period, tumor and lymph node stage, and adjuvant therapy (chemotherapy and/or radiotherapy) [ 8 ]. However, their findings may be affected by residual confounding from other dimensions of SEP, which were not incorporated in their study (e.g., income and employment).…”
Section: Discussionsupporting
confidence: 86%
“…However, in Nordic countries, health inequality persists despite the build-up of the welfare states (also called the Nordic paradox) [ 7 ]. Studies set in Denmark, a country with tax-funded healthcare, report increased risks of breast cancer recurrence (and other cancer types) among patients with low education and in those living alone [ 8 ], and a higher 5-year mortality in women with lower education and income [ 9 , 10 ], even after adjusting for tumor characteristics, treatment, and comorbidities [ 11 , 12 ]. The same tendency has been observed in other European countries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We need a better understanding of the symptom presentation in CR and SPC, and how patients and healthcare professionals react to new symptoms. Furthermore, considerations should be made on the best use of the limited resources in the healthcare system, and risk stratified follow-up pathways should be considered [48]. Studies have reported a false positive rate of 71% in tests, which all raised suspicion of CR [23], and a probability of 87% for at least one false positive test within five years of follow-up [49].…”
Section: Discussionmentioning
confidence: 99%
“…A further paper by Rasmussen et al () looks beyond diagnostic and treatment intervals—to “time to recurrence”, for malignant melanoma, bladder, lung, ovarian, endometrial, colorectal and breast cancer in patients in Denmark. They found that lower educational level, living alone and comorbidity were associated with shorter time to recurrence.…”
mentioning
confidence: 99%